Image visualisation and classification of MODIS/ASTER Airborne Simulator (MASTER) remotely sensed data for agricultural area - Teoh, Chin Chuang, Dr.; Shattri, Mansor; Abdul Rashid, Mohamed Shariff; Noordin, Ahmad (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/